Kesejahteraan Anak Adopsi Usia Prasekolah (3-5 Tahun) - Eko Setiawan; R. Nunung Nurwati; Nurliana Cipta Apsari (PERSPEKTIF, 2021)
Child welfare is the responsibility of the family because the child is part of the family. However, in reality there are still many who neglect their children so that the children's welfare is threatened. Abandoned children need protection to ensure their survival. One of the efforts made in dealing with the problem of neglected children is through an institution-based child service program through child social service institutions. However, institution-based child services have not been optimal in realizing children's welfare. Thus, children who are in institution-based care need to be transferred to family-based care so that the child's welfare can be better. One of the permanent efforts to care for children is through adoption. The method used in this research is mixed methods research method. The design chosen in this study is Explanatory Sequential Mixed Methods, the researcher will measure the level of children's welfare with quantitative research first followed by qualitative research. The results of quantitative research regarding the welfare of preschool adopted children show that basically the welfare of adopted children is in the good category. The results of the qualitative research found that the background and reasons or motivation of adoptive parents to adopt an effect on the care of the adopted child so that the child's welfare can be better. Most adoptive parents do not yet have biological children, so the presence of adopted children is a complement to their long-awaited family. The opportunity they get for adoption makes them try to care for, nurture, and treat their adopted child very well. They always pay attention to children's physical development, children's psychological development, children's social development and children's cognitive development so that children's welfare can be achieved.